(OPTIMALISASI MEDIA SOSIAL DALAM MEMPERKENALKAN PRODUK LOKAL SECARA DIGITAL DI DESA CISOLOK) - Anne Sandra Dewi; Rida Bareta (STISIP Widyapuri Mandiri Sukabumi, 2023)
Cisolok Village is a village with a geographical location bordering the Indonesian Ocean. It has the potential for marine tourism and supporting MSMEs. The digital marketing branding seminar with the theme of optimizing social media in introducing local products digitally is one of the efforts made in Community Service activities to be able to increase the insight of Cisolok Village MSME players to recognize digital marketing branding in the hope of increasing product recognition to the wider community and increasing sales profits. The Cisolok Village digital marketing branding seminar was held on Tuesday, August 08, 2023 at the Cisolok Village Office Hall with presenters Imelda D.S SE (Mother of UMKM Sukabumi), Herman Subandi S,Ip M.Si (DKUKM representative), and Rosita Juliyanti, S.I.Kom (online import clothing entrepreneur). The seminar was attended by participants from the Sukabumi UMKM association in Cisolok Village, as well as village officials, hamlet heads, neighborhood heads, PKK cadres and Posyandu cadres. Digital marketing branding is important for UMKM players because it can more easily promote their businesses due to wider reach, more efficient costs, direct interaction online (cyberspace) with consumers, and also the ease for entrepreneurs in choosing specific targets or potential customers according to the criteria of the business being undertaken.